Analisis Germane Load Dilihat darı Minat Belajar Dan Kemampuan Awal Matematıka Siswa SMA di Kelas Virtual - Avianti Permata Yuniar; Aan Hendrayana; Syamsuri Syamsuri (Universitas Mathla'ul Anwar Banten, 2022)
Learning carried out with virtual classes during the COVID-19 pandemic is important for evaluation so that in the future the gradual process towards normal learning conditions can take place properly and according to learning objectives. This study aims to describe the germane load as seen from the interest in learning and the initial mathematical ability of high school students in a virtual classroom. This research was conducted at SMA Negeri 1 Cikande using a descriptive qualitative approach involving 7 students from 31 students of class XI IPA as research subjects who were selected by seeing the result of learning interest on virtual class and early ability of mathematics. Data collection was obtained from the results of interest in learning questionnaires, end of semester assessment results, math problem solving tests, observations, interviews, and documentation. The results showed that students with different learning interests and initial abilities had different germane loads as indicated by their mental effort and problem solving results.